An improved harmonic current detection method based on LMS - Xue Zhang; Lei Wu; Jing Hui (2015 IEEE 10th Conference on Industrial Electronics and Applications (ICIEA), 2015)
In the harmonic detection circuit, the precision of detection of harmonic current is crucial to the realization of the entire circuit's function. By using the combination of the adaptive theory and the traditional instantaneous reactive power theory, extraction of fundamental current using the LMS adaptive algorithm improve filtering accuracy and shorten the delay time compared with the low pass filter, the accuracy of detecting current is further improved.